SEONT: Agricultural Household Survey Ontology - CGIAR Platform for Big Data in Agriculture (2020)
A first module of the SEONT ontology was developed based on the extraction of concepts and variables from the '100 core questions' and from reference existing ontologies. A study case was performed with IRRI survey data about rice variety adoption to test SEONT content and validate ML concept extraction algorithm